Reducing the cost of preventive maintenance (PM) through adopting a proactive reliability-focused culture. - Eti, Mark C.; Ogaji, Stephen O. T.; Probert, Sydney D. (Elsevier, 2006)
The economic and political realities of the 1990s forced managers to reverse long-standing organizational cultures in order to reduce costs and energy expenditures in their organisations. For instance, these can be achieved, with respect to maintenance, by replacing a reactive repair-focused attitude by a proactive reliability-focused culture. Thereby far less (i) human effort is expended and (ii) energy would be wasted, both of which lead to increased profitability.
Keywords: Cost reduction; PM; Culture; Best practice; Nigerian industries